1991
DOI: 10.1164/ajrccm/144.5.1091
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of Beat Frequency in Respiratory Ciliated Cells: Demonstration by Viscous Loading

Abstract: As opposed to the virtually constant load exerted by water on the cilia of ciliated protozoa, the hydrodynamic load on respiratory cilia can undergo broad variations because of changes in the rheologic properties of mucus. When water-rowing ciliated cells are exposed to increased viscosity (1 to 50 cP), their beat frequency decreases exponentially. According to Newton's fluid dynamic theory, this outcome is expected for an engine that generates constant force. However, the findings reported here indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 8 publications
8
39
0
1
Order By: Relevance
“…As mucus viscosity around the cilia (i.e. the load on the system) increases, ciliary mechanics are adjusted so as to maintain a ciliary beat frequency, albeit somewhat reduced, that is sufficient to maintain transport of mucus (containing trapped pathogens and particulates) to the larynx, where it is swallowed or expectorated (Johnson et al, 1991). Cytosolic Ca 2+ levels play an important role in this process of autoregulation, and increases in cytosolic Ca 2+ are associated with changes in ciliary beat frequency (Salathe, 2006).…”
Section: Motile Cilia In the Mammalian Respiratory Epithelium Exhibitmentioning
confidence: 99%
“…As mucus viscosity around the cilia (i.e. the load on the system) increases, ciliary mechanics are adjusted so as to maintain a ciliary beat frequency, albeit somewhat reduced, that is sufficient to maintain transport of mucus (containing trapped pathogens and particulates) to the larynx, where it is swallowed or expectorated (Johnson et al, 1991). Cytosolic Ca 2+ levels play an important role in this process of autoregulation, and increases in cytosolic Ca 2+ are associated with changes in ciliary beat frequency (Salathe, 2006).…”
Section: Motile Cilia In the Mammalian Respiratory Epithelium Exhibitmentioning
confidence: 99%
“…14 It appears that respiratory ciliated cells have a functional reserve that permits them to auto regulate their mechanical output in response to changing respiratory mucus viscosity. 15 The dynamic viscoelastic properties of nasal mucosa determined by oscillary rheometry has revealed significant improvement in elasticity after repeated antral lavages in chronic sinusitis. 16 It is hypothesized that it improves mucociliary function, decreases mucosal oedema and inflammatory mediators and mechanically clears inspissated mucus.…”
Section: Discussionmentioning
confidence: 99%
“…Although water-propelling cilia do appear to be able to adapt to increasing viscosity they do not appear to be as well adapted as mucous propelling respiratory cilia [9]. Johnson and colleagues [9] found that mucous propelling cilia of the respiratory tract from confluent clusters of cells or single cells showed autoregulatory properties when exposed to an increased viscous load.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and colleagues [9] found that mucous propelling cilia of the respiratory tract from confluent clusters of cells or single cells showed autoregulatory properties when exposed to an increased viscous load. Despite the use of viscous loads, that were considerably higher (1-150cP) than those used in our experiments, the beat amplitude and frequency exhibited only slight variations over viscosities ranging from 12-150cP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation